Answer:
x=5+1/2
Explanation:
4x-2(x-5)=3(2x-4)
We move all terms to the left:
4x-2(x-5)-(3(2x-4))=0
We multiply parentheses
4x-2x-(3(2x-4))+10=0
We calculate terms in parentheses: -(3(2x-4)), so:
3(2x-4)
We multiply parentheses
6x-12
Back to the equation:
-(6x-12)
We add all the numbers together, and all the variables
2x-(6x-12)+10=0
We get rid of parentheses
2x-6x+12+10=0
We add all the numbers together, and all the variables
-4x+22=0
We move all terms containing x to the left, all other terms to the right
-4x=-22
x=-22/-4
x=5+1/2